Vaccination against influenza in pregnant women in a maternity hospital in the Czech Republic in the season 2020-2021 - Kynčl, Jan; Liptáková, Monika; Košťálová, Jana; Malý, Marek; Křížová, Marcela; Heřman, Hynek; Fabiánová, Kateřina (BMC public health, 2023)
OBJECTIVES: Pregnant women are among the priority groups to receive influenza vaccines in the Czech Republic since 2011, data on vaccination coverage are not yet available. The aim of the study was to determine the influenza vaccination coverage (IVC) and provide source data for further activities. METHODS: A prospective observational study was performed in a large maternity hospital in Prague. The self-completed questionnaire was distributed to 5,475 pregnant women between September 1, 2020 and August 31, 2021. Questions included maternal sociodemographic characteristics, influenza vaccination status and sources of maternal vaccination recommendations during pregnancy. RESULTS: A total of 4,617 completed questionnaires have been analysed. The median age of study participants (N = 4,592) was 33 years (range: 18-51 years). The majority (69.7%) of women had completed their university education, most women were childless (58.5%) or had one child (32.5%) before the start of the study. Less than 2% of women reported being vaccinated against influenza during their pregnancy (1.5%; 95% CI, 1.1-1.9%). Only 21% of women knew that it's possible to get vaccinated against influenza during pregnancy. Participants considered influenza vaccination in pregnancy as important (3.3%), useful (41.1%) and useless (44.4%). Out of 959 pregnant women who had information about influenza vaccination during pregnancy, only 6.9% were vaccinated, while among those who did not have this information, 0.1% were vaccinated during pregnancy (p < 0.001). The most frequent source of information was Internet, then media and a general practitioner. CONCLUSIONS: The IVC during pregnancy in our study was extremely low. In order to improve IVC among pregnant women, it is necessary to increase awareness of recommendations and vaccination options among the public and professionals and incorporating vaccination recommendation in routine antenatal practice.
Keywords: dospělí; těhotenství; Humans; lidé středního věku; těhotné ženy; Middle Aged; Health Knowledge, Attitudes, Practice; Influenza Vaccines; chřipka lidská; mladý dospělý; Hospitals, Maternity; roční období; Czech Republic; Pregnancy Complications, Infectious; Pregnant People; zdraví - znalosti, postoje, praxe; Surveys and Questionnaires; Influenza, Human; Česká republika; Adult; Adolescent; průzkumy a dotazníky; Seasons; ženské pohlaví; lidé; infekční komplikace v těhotenství; mladiství; Pregnancy; Vaccination; porodnice; vakcíny proti chřipce; Young Adult; vakcinace; Female